A competitividade do Brasil, dos Estados Unidos da América (EUA) e da Argentina nas exportações de milho no período 2000-2015 - Paula, Cristiano Villanova de (Universidade do Vale do Rio dos Sinos, 2017)
The objective of this study was to analyze the competitiveness of Brazilian exports in the global corn market from 2000 to 2015 compared to the United States of America (USA) and Argentina. The methodology used in the research was based on the Revealed Comparative Advantage Index and the Specialization Index. The results showed that Brazil did not comparative advantage revealed in only two years, 2000 and 2005 in corn except for sowing and in 2001 and 2003 in corn for sowing. In relation to the Specialization Index, the results show that Brazil has no specialization in any of the years of the analyzed period in relation to Argentina in both products. In relation to the USA, Brazil has export specialization in corn except for sowing in half of the analyzed years, especially the years 2013 and 2015, and in corn for sowing Brazil has export specialization in some specific years, highlighting the years of 2010, 2011, 2012 and 2015 as relatively more specialized. Finally, despite the US world supremacy in the production and export of corn, and Argentina's competitiveness on the global stage, Brazil has the potential to remain one of the world's largest exporters of this commodity.
Keywords: Brasil; Exportação; Competitividade; Milho; Brazil; Export; Competitiveness; Corn; ACCNPQ::Ciências Sociais Aplicadas::Economia